A STUDY OF BEST PRACTICE IN APPLYING LIKAY FOR CHILDREN’S LEARNING: A CASE STUDY OF NARESUAN HUAY PHUENG SCHOOL, PRACHUAP KHIRI KHAN PROVINCE - Kanthong, Pornsaran (Journal of Social Science and Cultural, 2023)
This research aimed at 1) studying the transferring Likay performance for students at Naresuan Huay Phueng School, Prachuap Khiri Khan Province; 2) examining guidelines for applying Likay as learning media for the students studying in subject areas of Thai; Social Studies, Religion, Culture; and Art; at Naresuan Huay Phueng School; and 3) applying the best practice of Likay as learning media for student’s learning in subject areas of Thai; Social Studies, Religion, Culture; and Art in the target school. The research employed a mixed method. The data derived from 1) in-depth interview with interviewees including the leader of Thai Culture Conservation Club, a classical dance teacher, a teacher, and students of Naresuan Huay Phueng School; and 2) Exhibited LiKay about Phaya Nakin and questionnaires administered to respondents, including 2 teachers and grade 6 students of the target school i.e. Ban Nong Plub (Intajit Bamrung) School. The qualitative data were analyzed by using content analysis. The descriptive statistics used for quantitative data analysis were mean and standard deviation. The results of the research found that 1) The transferring Likay performing art consists of the knowledge providers and knowledge recipients; content; and method. 2) Guidelines for applying Likay as learning media for students establishing Thai Culture Conservation Club. Operations 2.1) Hold a meeting of teachers of social studies subject groups; define learning units to create Likay purposes; 2.2) Implement plans to organize learning activities; 2.3) Teachers, students, and audience members evaluated the Likay performance. 2.4) Disseminate Likay performance in various occasions. Application of Likay as learning media for student learning included 6 topics that were integrating to subject areas as followed: the integration to in subject areas of Thai; Social Studies, Religion, Culture; and Art. 3) Applying the best practice of Likay as learning media for students of Ban Nong Plub (Intajit Bamrung) School was at a high level.